Efficacy of Two Cognitive-Behavioral Treatment Modalities for Panic Disorder With Nocturnal Panic Attacks. (September 2013) - Marchand, Lyne; Marchand, André; Landry, Pierre; Letarte, Andrée; Labrecque, Joane
The aim of this research was to examine the efficacy of two cognitive-behavioral treatment modalities for panic disorder (PD) with nocturnal panic (NP). The first study was conducted to determine whether conventional CBT for PD was effective for PD with NP in three participants. A second study sought to explore whether a CBT adapted to NP would lead to different clinical outcomes in three other participants. A multiple-baseline single-case design across individuals was used in both studies. Treatment outcome was assessed with standardized clinician ratings, self-report questionnaires, and daily self-monitoring. Results revealed that both the conventional and the adapted treatments showed a faster decrease in NPs versus daytime panics and significant clinical changes in all measures for up to a year after therapy. Hence, the changes brought about by the adapted treatment seemed to be similar to those obtained using conventional treatment. In light of these results, it can be presumed that conventional strategies may be sufficient for the treatment of NP. These observations raise questions regarding the real need to adapt treatments specifically to NP.